Embryology of the naso‐palatal complex in Gekkota based on detailed 3D analysis in Lepidodactylus lugubris and Eublepharis macularius. Issue 2 (10th November 2020) - Kaczmarek, Paweł; Metscher, Brian; Rupik, Weronika
Abstract: The vomeronasal organ (VNO), nasal cavity, lacrimal duct, choanal groove, and associated parts of the superficial (soft tissue) palate are called the naso‐palatal complex. Despite the morphological diversity of the squamate noses, little is known about the embryological basis of this variation. Moreover, developmental data might be especially interesting in light of the morpho‐molecular discordance of squamate phylogeny, since a 'molecular scenario' implies an occurrence of unexpected scale of homoplasy also in olfactory systems. In this study, we used X‐ray microtomography and light microscopy to describe morphogenesis of the naso‐palatal complex in two gekkotans: Lepidodactylus lugubris (Gekkonidae) and Eublepharis macularius (Eublepharidae). Our embryological data confirmed recent findings about the nature of some developmental processes in squamates, for example, involvement of the lateral nasal prominence in the formation of the choanal groove. Moreover, our study revealed previously unknown differences between the studied gekkotans and allows us to propose redefinition of the anterior concha of Sphenodon . Interpretation of some described conditions might be problematic in the phylogenetic context, since they represent unknown: squamate, nonophidian squamate, or gekkotan features. Abstract : We used X‐ray microtomography and light microscopy to describe morphogenesis of the naso‐palatal complex in two gekkotans: Lepidodactylus lugubris (Gekkonidae) and Eublepharis macularius (Eublepharidae). Our embryological data confirmed recent findings about the nature of some developmental processes in squamates and revealed previously unknown differences between the studied gekkotans. We also proposed redefinition of the anterior concha of Sphenodon .